Mental Health Recovery and Economic Recovery after the Tsunami : High-Frequency Longitudinal Evidence from Sri Lankan Small Business Owners - de Mel, S. (2012)
A sample of 561 Sri Lanka microenterprise owners affected to various extents by the December 2004 Indian Ocean tsunami were surveyed five times at quarterly intervals between March 2005 and April 2006. Mental health recovery was measured through questions on return to normalcy and change in life outlook. Business profits were used to measure livelihoods recovery. We find that these mental health process measures are correlated with post-traumatic stress disorder and general mental health in a validation survey, and display similar correlates to both in the cross-section. However, socioeconomic factors are not found to be significant in predicting the dynamics of mental health recovery in a fixed effects logistic regression. Mental health recovery from a given initial level therefore appears to depend largely on time since the disaster, and not on economic recovery of an individual's livelihood. (c) 2007 Elsevier Ltd. All rights reserved.